2004
DOI: 10.1017/s1357729800054643
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal fermentation, methanogenesis and nitrogen utilization of sheep receiving tropical grass hay-concentrate diets offered withSapindus saponariafruits andCratylia argenteafoliage

Abstract: The effects of supplementing a tropical, low-quality grass hay (Brachiaria dictyoneura) with legume foliage (Cratylia argentea) or fruits of the multipurpose tree Sapindus saponaria on ruminal fermentation, methane release and nitrogen (N) utilization were evaluated. Six Swiss White Hill lambs were used in a 6 ✕ 6 Latin-square design with a 3 ✕ 2 factorial arrangement of treatments with measurements of energy metabolism being conducted using open-circuit respiratory chambers. Treatments consisted of three basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Moreover, in the previous studies mentioned reported that feed supplement as the fodder tree mixture would could be enhanced ruminal degradation of nutrients, volatile fatty acids, and microbial growth in the ruminants [12]. An initial in vitro study demonstrated that supplementation of a low-quality roughage with different kind of tropical fodder such as Arachis pintoi and Cratylia argentea significantly enhanced rumen microbial activity and increased the extent of ruminal organic matter (OM) and fiber degradation [13]. In in vivo study, Viennasay et al [14] currently reported that supplementation of fodder shrub (Flemingia) enhanced the nutrient digestibility, feed intake and microbial protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the previous studies mentioned reported that feed supplement as the fodder tree mixture would could be enhanced ruminal degradation of nutrients, volatile fatty acids, and microbial growth in the ruminants [12]. An initial in vitro study demonstrated that supplementation of a low-quality roughage with different kind of tropical fodder such as Arachis pintoi and Cratylia argentea significantly enhanced rumen microbial activity and increased the extent of ruminal organic matter (OM) and fiber degradation [13]. In in vivo study, Viennasay et al [14] currently reported that supplementation of fodder shrub (Flemingia) enhanced the nutrient digestibility, feed intake and microbial protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of feed additives have been tested for their potential to mitigate methane emissions from ruminants [9,10]. Natural plant secondary compounds such as tannins, saponins, and essential oils are among the promising feed additives to mitigate enteric methane emission, and they have been repeatedly investigated [11][12][13][14][15]. For instance, extracted and purified tannins, either condensed (from mimosa and quebracho) or hydrolysable (from chestnut and sumac), added at levels of 0.5-1.0 mg/mL, were shown to substantially decrease the methane per unit of digestible organic matter and methanogen population [16].…”
Section: Introductionmentioning
confidence: 99%
“…In general, an appropriate proportion of leguminous forage in a diet is considered to be effective for mitigating CH 4 emission in beef cattle (Hess et al., 2004). This is because legumes are rich in secondary metabolites, such as saponins and tannins, which have potential to inhibit the activity of protozoa and methanogen in the rumen (Beauchemin et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The higher feeding level could lead to a faster outflow rate of feedstuff from the rumen (AFRC, 1993), therefore, shifts part of the digestion from rumen to hindgut. The hindgut fermentation has a lower CH 4 production than the ruminal fermentation (Fievez et al., 1999; Hess et al., 2004). However, the CH 4 :DMI (Figure 1b) in the AH‐24 group was higher than that in the AH‐16 group under the same feeding level (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation